(untitled) (Journal of Parents and Teachers, 2014)
Teaching card of the film Persepolis, autobiographical story directed by the Iranian Marjane Satrapi and the French Vincent Paronnaud. This film works with values such as what is good, what is bad, being a hero and also some current issues such as politics, integrist Islamic regimes and emigration. As usual, there are activities to do before watching the film, meanwhile and after watching the film.